2016
DOI: 10.1186/s12862-016-0754-5
|View full text |Cite
|
Sign up to set email alerts
|

Inconsistent phylogeographic pattern between a sperm dependent fish and its host: in situ hybridization vs dispersal

Abstract: BackgroundCo-dispersal of sperm-dependent hybrids and their sexual relatives is expected to result in consistent spatial patterns between assemblages of hybrids and genetic structure of parental species. However, local hybridization events may blur this signal as assemblages could be organized under different connectivity constraints. This study aims at testing the hypothesis of local hybridization events by comparing the assemblage of hybrid fish Chrosomus eos-neogaeus to the genetic diversity of one of its p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
41
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
5

Relationship

4
1

Authors

Journals

citations
Cited by 14 publications
(41 citation statements)
references
References 91 publications
0
41
0
Order By: Relevance
“…The very high diversity of lineages and their restricted distribution are consistent with the hypothesis that hybridization events occurred locally. Genetic analyses provided another support to this hypothesis as the multilocus genotype of hybrids from RI, YA, and SF networks matched that of C. eos sympatric populations, one of the species involved in hybridization (Vergilino et al, ).…”
Section: Discussionmentioning
confidence: 89%
See 3 more Smart Citations
“…The very high diversity of lineages and their restricted distribution are consistent with the hypothesis that hybridization events occurred locally. Genetic analyses provided another support to this hypothesis as the multilocus genotype of hybrids from RI, YA, and SF networks matched that of C. eos sympatric populations, one of the species involved in hybridization (Vergilino et al, ).…”
Section: Discussionmentioning
confidence: 89%
“…This striking result contrasts with diversity from the other regions of North America surveyed so far. Previous studies reported a single or a very low number of widespread lineages per region (Angers & Schlosser, ; Doeringsfeld, Schlosser, Elder, & Evenson, ; Elder & Schlosser, ; Goddard et al, ; Vergilino et al, ). Such a low diversity in very large areas is typical of mtDNA diversity of species that colonized regions covered by the ice sheet during the Pleistocene (Bernatchez & Wilson, ).…”
Section: Discussionmentioning
confidence: 94%
See 2 more Smart Citations
“…Thereafter, mtDNA of all individuals was discriminated between C. eos (wild type) and C. neogaeus (cybrid). Because several C. neogaeus haplotypes were present in cybrids of this lake (Vergilino, Leung, & Angers, 2016), these individuals were further discriminated to select a single cybrid mitotype (Mississippian, A‐IV). The genetic identification is further described below.…”
Section: Methodsmentioning
confidence: 99%